A Case Report of Management of Medulloepithelioma of the Ciliary Body and Iris without Recurrence over an Observation Period of Twenty Years - N. Eide; J. Navaratnam; P. Jebsen (Case Reports in Ophthalmological Medicine)
Intraocular medulloepithelioma is a rare embryonal tumor that is believed to arise from the epithelium of the medullary tube. We report a 37-year-old female with medulloepithelioma presented at the age of 17 with a one-month history of left-sided visual deterioration and visible iris lesion. Birth history and medical and family histories were insignificant. The left eye revealed a vascularized iris mass. Further examination revealed a grey-white ciliary body mass and a subluxated lens with best-corrected visual acuity (BCVA) of 0.5. The patient underwent partial lamellar corneo-sclerouvectomy. The histological and electron microscopic findings revealed medulloepithelioma. To reduce the risk of recurrence of the probable malignant tumor, she was treated with Ruthenium plaque therapy about six weeks following surgical removal. Pars plana vitrectomy and lensectomy with laser photocoagulation of the peripheral retina were performed at the removal of the brachytherapy plaque. She regained her BCVA of 1.0 in her left eye 3.5 months following pars plana vitrectomy. At 20-year follow-up, no tumor recurrence was seen and her BCVA remained 1.0.